(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Prosthetic joint infection (PJI) represents one of the most challenging complications of total hip and knee arthroplasty. It increases morbidity, prolongs hospital stay, and imposes a significant economic burden. Identifying the frequency of PJI and its association with patient characteristics in local healthcare settings remains crucial for developing effective prevention and management strategies. Methods: We carried out a cross-sectional study of 164 patients who underwent total hip or knee arthroplasty at a tertiary care hospital. We collected demographic, socioeconomic, and clinical data, including comorbidities and lifestyle factors. We determined the frequency of PJI and examined the baseline characteristics of the cohort. Results: PJI occurred in 7.3% of patients (12 cases). Most patients were aged 46–70 years (53%), while 47% were between 20 and 45 years. The gender distribution was almost equal, with 50.6% males and 49.4% females. Comorbidities were frequent: 54.3% had diabetes mellitus, 49.4% had hypertension, and 51.8% had dyslipidemia. Smoking was also common (47%). Most participants came from higher-income households (84.8%), while 15.2% reported lower income. Educational attainment varied, with 23.8% illiterate and 29.3% having higher education. Conclusion: We identified a notable frequency of PJI in this data set. Comorbidities and lifestyle factors contributing to infection risk. These findings emphasize the need to strengthen perioperative optimization and infection-prevention strategies.